The in vivo and in vitro interactions of elastic and rigid vesicles with human skin - Loan Honeywell-Nguyen, P; de Graaff, Anko M; Wouter Groenink, H.W; Bouwstra, Joke A (Biochimica et biophysica acta, 2002)
Elastic vesicles are the most novel development in vesicular systems design for dermal and transdermal drug delivery. However, interactions between these vesicles and human skin are not yet fully understood. In this study, the in vivo and in vitro interactions between elastic-, rigid vesicles and micelles with human skin were investigated. Vesicle and micelle solutions were applied onto human skin in vitro and in vivo. Subsequently, a series of tape strippings were performed, which were visualised by freeze fracture electron microscopy (FFEM). The results showed no ultrastructural changes in skin treated with rigid vesicles. Skin treated with elastic vesicles, however, showed a fast partitioning of intact vesicles into the deeper layers of the stratum corneum (SC), where they accumulated in channel-like regions. Only little vesicle material was found in the deepest layers of the SC, suggesting that the partitioning of intact vesicles from the SC into the viable epidermis is unlikely to happen. Treatment with micelles resulted in rough, irregular fracture planes. Similar results were obtained in vitro and in vivo, indicating an excellent in vitro/in vivo correlation. These results support the hypothesis that elastic vesicles have superior characteristics to rigid vesicles for the interaction with human skin. Elastic vesicles and micelles demonstrated very different interactions with human skin and hence probably also have different mechanisms of action for the enhancement of drug transport.